Haematuria: An Imaging Guide - Moloney, Fiachra (Hindawi Publishing Corporation, 2014)
This paper discusses the current status of imaging in the investigation of patients with haematuria. The physician must rationalize imaging so that serious causes such as malignancy are promptly diagnosed while at the same time not exposing patients to unnecessary investigations. There is currently no universal agreement about the optimal imaging work up of haematuria. The choice of modality to image the urinary tract will depend on individual patient factors such as age, the presence of risk factors for malignancy, renal function, a history of calculus disease and pregnancy, and other factors, such as local policy and practice, cost effectiveness and availability of resources. The role of all modalities, including conventional radiography, intravenous urography/excretory urography, ultrasonography, retrograde pyelography, multidetector computed tomography urography (MDCTU), and magnetic resonance urography, is discussed. This paper highlights the pivotal role of MDCTU in the imaging of the patient with haematuria and discusses issues specific to this modality including protocol design, imaging of the urothelium, and radiation dose. Examination protocols should be tailored to the patient while all the while optimizing radiation dose.